KAJIAN SOSIAL EKONOMI PETANI CAP TIKUS DI DESA WUWUK KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Wuisan, Miranti Friyana; Kaihatu, Jolanda Esther; Poli, Ellen Eva; Tewal, Selvana Treny Rosita; Lobja, Xaverius Erick; Gumilang, Cahya (Jurnal Social Science, 2025)
This study aims to determine the socio economic study of cap tikus farmers in Wuwuk Village Tareran District South Minahasa Regency This study uses a qualitative descriptive method Data collection techniques used are observation interviews documentation The results of the study indicate that: 1 The level of education of cap tikus farmers in Wuwuk Village is in the middle category 2 The income of cap tikus farmers is an average of IDR 4 000 000 month with the highest income of IDR 6 000 000 month and the lowest IDR 2 700 000 month 3 The level of consumption or expenditure of cap tikus farmers per month is at least around IDR 3 000 000 and at most IDR 7 000 000 which is for daily needs 4 Ownership of assets or land used by farmers for processing cap tikus still uses land owned by other people 5 Farmers access to the cap tikus processing site is poor because of uneven development in this case some roads are already concrete and some are still dirt 6 Marketing of captikus in Wuwuk Village is still limited because farmers only sell cap tikus to collectors and some of them sell retail at their homes < em>< p>